2007
DOI: 10.1007/s10450-007-9072-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-templated organosilicas with hexagonally ordered mesopores: the effect of organosilane addition at different synthesis stages

Abstract: Two series of ordered mesoporous organosilica (OMO) SBA-15 materials with surface and bridging groups were fabricated by varying the organic precursor addition at different synthesis stages. The consequence of the delayed introduction of organic precursor on the structural and adsorption properties of the resulting OMOs was investigated. The OMOs studied were synthesized via co-condensation of tetraethyl orthosilicate (TEOS) and ureidopropyltrimethoxysilane (UPS) as well as TEOS and bis(triethoxysilylpropyl) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…To summarize, generally, the increase of disulfide‐bridged organosilane content in the initial premixed silanes results in the increase of disulfide‐bridged silsesquioxane content in the framework; however, it also caused a decrease of the pore size, pore volume, specific surface area, and mesopore ordering . The structural change is attributed to the fact that the high content of disulfide‐bridged organosilane with a hydrophobic chain interacts with the hydrophobic part of the surfactant template, thus interfering with their cooperative self‐assembly and condensation.…”
Section: Controlled Synthesis Of Hybrid Nanomaterials With Disulfide‐mentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, generally, the increase of disulfide‐bridged organosilane content in the initial premixed silanes results in the increase of disulfide‐bridged silsesquioxane content in the framework; however, it also caused a decrease of the pore size, pore volume, specific surface area, and mesopore ordering . The structural change is attributed to the fact that the high content of disulfide‐bridged organosilane with a hydrophobic chain interacts with the hydrophobic part of the surfactant template, thus interfering with their cooperative self‐assembly and condensation.…”
Section: Controlled Synthesis Of Hybrid Nanomaterials With Disulfide‐mentioning
confidence: 99%
“…The formation of mesopores is mainly achieved by employing triblock copolymer poly(ethylene oxide) 20 –poly(propylene oxide) 70 –poly(ethylene oxide) 20 (EO 20 PO 70 EO 20 , P123, M a = 5800) or the cationic surfactant cetyltrimethylammonium bromide (CTAB)/cetyltriethylammonium bromide (CTEAB) as templates, as compiled in Table 1 . For the P123 template, Zhang et al reported the first synthesis of ordered mesoporous organic–inorganic composites with disulfide‐bridged organosilica framework by one‐step co‐condensation of BTEPTS and TEOS, in order to generate materials for Hg 2+ adsorption with high selectivity and capacity .…”
Section: Controlled Synthesis Of Hybrid Nanomaterials With Disulfide‐mentioning
confidence: 99%
“…14 Introduction of a variety of organic groups ranging from small ones such as ethane [15][16][17][18] to larger ones such as disulde and isocyanurate has been achieved in the case of SBA-15 and SBA-16 silica mesostructures. [17][18][19] In this study, tris [3-(trimethoxysilyl)propyl] isocyanurate (ICS), a nitrogen-containing silane, was used to prepare composite materials. The ICS-containing mesoporous silicas were used for adsorption of heavy metal ions, [20][21][22] and related environmental applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that in the case of cubic mesoporous materials the removal of polymeric template may be very challenging [48]. Notably, there are many reports on the template removal by extraction [17], calcination [4], supercritical fluid extraction [49], microwave irradiation [50], photocalcination [51] and a two step recipe involving extraction followed by calcination at elevated temperature that is suitable for the decomposition of the polymer [52]. Especially, extraction combined with calcination at appropriate temperature was found to be an effective procedure to remove the template without pore structure shrinkage and degradation of functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…OMOs can be synthesized by two major strategies including direct co-condensation [17][18][19][20][21][22][23][24][25] and post-grafting methods [26][27][28]. Co-condensation approach is especially attractive alternative to the grafting due to the possibility of incorporation of high loadings of organic groups, cost-effectiveness and simplicity of the process.…”
Section: Introductionmentioning
confidence: 99%